Reliability and validity of the Japanese version of the Emotion Regulation Skills Questionnaire - Fujisato, Hiroko; Ito, Masaya; Takebayashi, Yoshitake; Hosogoshi, Hiroki; Kato, Noriko; Nakajima, Shun; Miyamae, Mitsuhiro; Oe, Yuki; Usami, Satoshi; Kanie, Ayako; Horikoshi, Masaru; Berking, Matthias (Journal of Affective Disorders, 2017)
Conclusions: The Japanese version of the ERSQ showed adequate reliability and validity.
Keywords: Emotion regulation; Assessment; Validity; Reliability; Culture; Mental disorder